„Bitewnik Łódzki 1914” – popularyzator pamięci o Wielkiej Wojnie - Centek, Barbara; Centek, Jarosław (Acta Universitatis Lodziensis. Folia Librorum, 2013)
In August 2009, two regionalists, Zbigniew Janeczek and Michał Jagiełło decided to create a periodical called „Bitewnik Łódzki 1914” (“Lodz's Battle Paper 1914”). Main goal of this magazine was to inform Lodz's citizens about Great War on Polish territories. This project was extremely successful – next issues followed and first one was even translated into Russian. Columns of this periodical are filled with popular-scientific texts about battle of Lodz or other topics connected with Great War. There are also reprints of official announcements from war times. Professional graphics design of the periodical is also worth mentioning. „Bitewnik Łódzki 1914” is still developing and one may have hope that it will be published in the future.